2016
DOI: 10.1071/hc15023
|View full text |Cite
|
Sign up to set email alerts
|

Patient awareness, knowledge and use of colchicine: an exploratory qualitative study in the Counties Manukau region, Auckland, New Zealand

Abstract: IntroductIon: Treatment of gout, specifically with colchicine, varies globally. Colchicine can be fatal due to its narrow therapeutic index and potential for interactions. In New Zealand, cases of intentional and unintentional colchicine overdose have been documented. AIms:To explore patients' knowledge on the use of gout medicines, and in particular their awareness of the maximum dose of colchicine, the dangers of colchicine overdose, and their opinions on restricting colchicine dispensing. The study also inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In addition to unauthorized access, inappropriate colchicine dosing for gout flares is the other situation that should be avoidable with education about the risks and benefits and the correct dosing of colchicine. People with gout report increasing the dose of colchicine in an attempt to control gout flares [ 86 ]. This has risks and it is important that people with gout know to seek medical attention if a gout flare fails to settle as expected with colchicine rather than simply taking more.…”
Section: Strategies To Minimize the Risk Of Poisoningmentioning
confidence: 99%
“…In addition to unauthorized access, inappropriate colchicine dosing for gout flares is the other situation that should be avoidable with education about the risks and benefits and the correct dosing of colchicine. People with gout report increasing the dose of colchicine in an attempt to control gout flares [ 86 ]. This has risks and it is important that people with gout know to seek medical attention if a gout flare fails to settle as expected with colchicine rather than simply taking more.…”
Section: Strategies To Minimize the Risk Of Poisoningmentioning
confidence: 99%
“…Rebello et al 5 found that patients poorly understand their gout medications and Humphrey et al 6 found that their GPs and nurses know this but do not really know what to do about it. Both studies develop suggestions to improve care for patients with gout.…”
Section: T Is the People Of Coursementioning
confidence: 99%